Route Optimization of Waste Carrier Truck using Breadth First Search (BFS) Algorithm - Muhammad Fahreal Bernov; Ani Dijah Rahajoe; Budi Mukhamad Mulyo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Waste problems have always been the main focus which still occurs in cities and regencies in Indonesia, andalso Sidoarjo Regency is no exception. Increasingly rapid population growth is one of the factors in the increasingpiles of waste in Sidoarjo Regency. The large number of villages with long distances and a large area means that wastecollection cannot be carried out on time, causing accumulation of waste that disrupts residents' daily activities. Thewaste transportation system in Sidoarjo Regency has so far not been optimal because there are still several problemswith the accumulation of waste in several sub-districts.In this study, an optimal route search system was created using the Breadth First Search and Depth First SearchAlgorithms as a search comparison in order to make it easier for Sanitation Service officers to carry out the wastetransportation process by considering the optimal destination location route according to input from the user. Theresults of this study will display information on the comparison of the total distance traveled and the total volumetraveled by the Breadth First Search and Depth First Search algorithms with different differences.